Treatment of landfill leachate using fenton process - Shabnam Khosravihaftkhany (School of Industrial Technology, Universiti Sains Malaysia, 2014)
One of the main problems in solid waste management in recent years is the increase of solid waste generated due to escalation of population. This results in the increase of leachate, which is the liquid that leaches out from the landfill. The production of leachate in landfills causes surface, water and ground water pollution, since leachate contains a lot of organic and inorganic compound which are difficult to treat. Researchers are still trying to find a good solution for treating leachate which is not only technically effective but also economically viable. In this paper, we discuss the use of Fenton process in the treatment of leachate. The effects of operation conditions such as reaction time, pH and H2O2 to Fe(II) ratio (W/W), on the efficiency of the Fenton process were investigated. The sample taken from the Pulau Burung landfill site (PBLS) in Penang, Malaysia has the concentration of COD at about 2800-3650 mgL-1. Results obtained indicated that the oxidation of organic materials in the leachate is pH dependent and the optimal pH is 3.0. The COD removal rate was increased with the increasing of reaction time until 240 min.